BIM SEBAGAI ALAT MANAGEMENT ASET : USULAN TINGKAT LOD DARI PEKERJAAN DIGITASI DAN VALIDASI PENGUKURAN ASSET PT.KAI - Dicky Arisikam; Heru Kuswanto; Muhammad Arifudin; Azwar Azwar (Jurnal Ilmiah Teknologi Infomasi Terapan, 2023)
The station is one of the important assets because passengers must access the station before boarding the train and must leave the station after arriving at their final destination. TTA is a unit that has one of the main tasks, namely collecting data, recording, validating, evaluating and controlling data on the Station Building assets. The main challenge in implementing an asset management strategy for buildings lies in the many types of assets that must be analyzed and categorized. Therefore, by adopting digital tools such as BIM, practitioners can improve the consistency of building information, computing capabilities, and coordination capabilities in managing assets. In the early stages, LOD is needed to determine the number and level of building information that needs to be placed in the BIM Model.The topic that will be presented in this paper is about proposing an LOD framework for station buildings managed by BUMN PT. Kereta Api Indonesia so as to improve the quality of asset management. Based on the research results, LOD contains 2 (two) key levels to identify a station building so that the resulting information becomes more structured when we want to build a BIM model. The first level is a component that is divided into several indicators such as roof components, walls, floors, doors, windows, ventilation, platforms, overcaping, rails, lighting and plumbing. The second level is elements which are divided into several descriptors such as geometry, position, dimensions, type, elevation, material, and finishing. So this paper proposes the LOD level to be applied to BIM so that it can explain station buildings from a simple model (LOD-S.KA. 0) to a detailed model (LOD-S.KA.4)